Promoción de estilos de vida activos (2005)
ABSTRACT: This article states the theoretical perspective for the physical activity promotion, implemented in the "Modelo de movilización social con énfasis en la actividad física para reducir el sedentarismo en las regiones de Antioquia, Quindío y Bogotá, D.C." research project, sponsored by COLCIENClAS and Ministerio de Protección Social. The physical activity prornotion was undertaken as a component of healthy life styles in the made model, since an ecological approach (attitude, social, cultural and urban development factors) and multilevel (person, group, cornmunity, institution, city), starting from the present health approaches, human performance and life quality and the most recent recommendations which come from the scientific evidences about this topic in the lastyears.